SAE Technical Paper Series 2007
DOI: 10.4271/2007-01-4037
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Poisoning and Regeneration of Pd Catalyst under Simulated Emission Conditions of Natural Gas Engine

Abstract: Palladium-based catalyst can be employed for natural gas exhaust clean up due to its high activity for light hydrocarbon oxidation. Unfortunately, trace amounts of sulfur in the natural gas feed severely deactivate the catalyst. In this paper, SO 2 adsorption over a monolithic Pd/Al 2 O 3 oxidation catalyst is monitored in a time-resolved manner in the presence of 100 ppm SO 2 under simulated aging conditions of a natural gas engine, which is correlated with the oxidation activity for CO and hydrocarbons such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…However, the sulfates produced on the alumina support would migrate to PdO x particles and cause another deactivation. It is just the migration of sulfates between PdO x and the alumina support that leads to catalysts only partial regeneration, as reported. , This migration explains the reappearance of alumina diffraction in the XRD pattern on the Reg.1 sample.…”
Section: Results and Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, the sulfates produced on the alumina support would migrate to PdO x particles and cause another deactivation. It is just the migration of sulfates between PdO x and the alumina support that leads to catalysts only partial regeneration, as reported. , This migration explains the reappearance of alumina diffraction in the XRD pattern on the Reg.1 sample.…”
Section: Results and Discussionsupporting
confidence: 62%
“…In other words, sulfur species can make the phase of α-Al 2 O 3 disappear and only rich-burn regeneration ( Reg.1 ) makes it reproduce. According to Hu et al, the maximum S/Pd atom ratio over unsupported PdO x is much smaller than the ratio of accumulated SO 2 and palladium observed over supported ones. They have concluded that SO 2 oxidation is catalyzed by PdO x , forming sulfate species selectively on the surface of PdO x particles, and the excess sulfates are believed to be transported to alumina sites.…”
Section: Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results are in good agreement with those calculated by Wang et al, where a chemisorption process was predicted for a series of electron-rich transition metals (Pd, Pt, Ag, and Au) doped in a MoSe 2 monolayer. One of the few studies addressing the SO 2 adsorption performances was reported by Hu and Williams . In this work, small Pd/PdO particles doped in an Al 2 O 3 matrix were experimentally studied as a natural gas cleaner.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few studies addressing the SO 2 adsorption performances was reported by Hu and Williams. 36 In this work, small Pd/PdO particles doped in an Al 2 O 3 matrix were experimentally studied as a natural gas cleaner. This palladium-aluminum-based matrix showed a nonreversible early saturation (30 min) in the presence of 100 ppm of SO 2 at 550 °C.…”
Section: Introductionmentioning
confidence: 99%